Implementation of Academic Supervision Activities as an Attempt to Improve Teacher Performance at SDN 023 Muara Mamat Baru Tapung in Kampar - Lindawati (Jurnal PAJAR (Pendidikan dan Pengajaran), 2023)
This paper discusses the improvement of teacher performance through the implementation of academic supervision activities. Teacher performance is a description of the teacher's attitudes, skills, values, and knowledge in implementing their duties and functions which consist of their appearance, actions, and work performance. The interviews and surveys conducted in the research aimed to obtain information regarding teacher performance in learning and related to the research. After analyzing the data, it can be concluded that the use of academic supervision indicates an improvement in teacher performance. The type of research was School Action Research (PTS), which was located at SDN 023 Muara Mahat Baru Tapung in Kampar. The research population was 9 teachers. Based on the research results, the implementation of academic supervision activities can improve teacher performance. It can be seen from the results of the first cycle at 56%, which were 54.5% of planning teacher ability learning, 63.6% of implementing teacher ability learning, and 54.5% of evaluating teacher ability learning. It increased to 85% in cycle II, which was 90.9% for planning teacher ability learning, 100% for implementing teacher ability learning, and 72.7% for evaluating teacher ability learning. It is classified in the very good category.